Fruit harvesting continuum manipulator inspired by elephant trunk - Tiefeng, Shao; Mingyu, Du; Guanjun, Bao; Libin, Zhang; Qinghua, Yang (International Journal of Agricultural and Biological Engineering, 2015)
By combining the investigation of the biomechanics and behavior of elephant trunk in the performance of a wide range of dexterous manipulations, a novel approach in the design and kinematics modeling of a fruit harvesting continuum manipulator was proposed. By comparing the structure of two different species of elephant trunk, a new continuum structure which matched the key features of elephant trunk was designed. Based on analysis of the underlying elephant trunk’s grasping mode, a novel kinematics model was proposed. Contrast to traditional robot kinematics which focused on end effector’s position and posture, the proposed continuum manipulator kinematics focus on the center of manipulator’s position and posture, which is more effective when trunk robot realizing grasp and establishes the foundation for its application. Finally, three typical grasping experiments were implemented. The experiment results showed that the manipulator could conduct wrap/pinch manipulations effectively for both small objects and bigger ones.DOI: 10.3965/j.ijabe.20150801.008Citation: Shao T, Zhang L B, Du M Y, Bao G J, Yang Q H. Fruit harvesting continuum manipulator inspired by elephant trunk. Int J Agric & Biol Eng, 2015; 8(1): 57－63.